In vitro antimicrobial activity and resistance mechanisms of cefiderocol against clinical carbapenem-resistant gram-negative bacteria - Yan, Ruyu; Ji, Jun; Wang, Liya; Zou, Yuerong; Shen, Han; Yuan, Jinhua; Cao, Xiaoli (Frontiers in Microbiology, 2025)
BackgroundThe rise of carbapenem-resistant gram-negative bacteria (CRGNB) necessitates new therapeutic options such as cefiderocol.ObjectiveTo evaluate the in vitro efficacy of cefiderocol against clinical CRGNB and investigate associated resistance mechanisms.MethodsA total of 370 CRGNB isolates were analyzed. Minimum inhibitory concentration (MIC) values were determined, and whole genome sequencing, efflux pump inhibition assays, and RT-qPCR were conducted to assess resistance-related mutations, gene loss, and expression changes.ResultsCefiderocol demonstrated potent in vitro activity, with high susceptibility rates in C. freundii (100%), K. pneumoniae (93.3%), and E. hormaechei (92.2%), and notable activity against P. aeruginosa (80.0%) and Escherichia coli (76.8%). Efflux pump inhibition by Carbonyl Cyanide m-Chlorophenyl Hydrazone (CCCP) significantly reduced MICs in resistant strains. Key resistance mechanisms included β-lactamase gene variants (blaOXA-66, blaOXA-23, blaSHV-12), mutations in envZ, cirA, nuoC, ampC, and loss or altered expression of iron transporter genes (piuA, pirA, fepA).ConclusionCefiderocol is highly effective against CRGNB; however, resistance may arise through diverse mechanisms, including efflux pump activity. Continued surveillance of emerging resistance is essential to guide its optimal clinical use.